Lipid metabolism of apoptotic vesicles accelerates cutaneous wound healing by modulating macrophage function - Yuan Qin; Xin Chen; Lili Bao; Lili Ren; Geng Dou; Jianing Lian; Shujuan Xing; Zihan Li; Feng Ding; Wen Qin; Xulin Liu; Bin Zhu; et al. (Journal of Nanobiotechnology)
Abstract The application of apoptotic extracellular vesicles (ApoEVs) derived from stem cell in skin wound healing has garnered significant attention. In recent decades, scholars have shown that extracellular vesicles (EVs) established intercellular communication by carrying proteins or microRNAs, the role of lipids in EVs in wound healing has yet to be clarified. Here, we focus on the key role of group X secretory phospholipase A2 (sPLA2-X) in lipid metabolism. Specifically, sPLA2-X significantly increased the production of the anti-inflammatory lipid mediators, resolvin D5 (RvD5), by hydrolyzing phospholipids in ApoEVs. This change not only promoted the uptake of ApoEVs by macrophages, but also effectively inhibited the expression of tumor necrosis factor-alpha (TNF-α) in macrophages, promoting the healing of skin wounds. In summary, this study contributes to our understanding of the mechanisms by which ApoEVs support skin defect repair and offers a potential theoretical approach for using ApoEVs in skin wound treatment. With further research and optimization, it is expected that more efficient and secure ApoEVs-based treatment strategies will be developed, bringing new breakthroughs in clinical treatment of skin injuries and related diseases. Graphical abstract